Clinical profile of pediatric neurotuberculosis patients at a tertiary care center of Western India - Ranvijay Singh; Nishitha Shetty; Maryam Naveed; Mridula Preetham Talari; Deepak Verma; Varsha Kulkarni (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study is to determine the clinical profile of neurotuberculosis in the age group of 6 months to 10 years and its association with biochemical analysis of cerebrospinal fluid (CSF) and neuroradiological findings. Methods: Retrospective assessment of the medical records of confirmed cases of neurotuberculosis from January 2010 to June 2014 was carried out. Results: Of the 46 cases studied, mean age at presentation was 3.4 years. Male-to-female ratio was 1.55:1. Fever, vomiting, headache, seizures, and focal neurological deficits were the most common presenting clinical symptoms. Protein-energy malnutrition (PEM) was detected in 39 cases. On systemic examination, the order of involvement of cranial nerves was VII, II, III, IV, VI, and V. Positive Mantoux test was present in only 11 cases. CSF findings showed lymphocytic predominance, raised protein levels with a decreased to normal glucose levels. Neuroimaging by computed tomography scan/magnetic resonance imaging of the brain gave a definite diagnosis in thirty cases of which hydrocephalus, basal exudates, tuberculoma, and infarctions were the most common findings. The primary focus of tuberculosis was found in the lungs on chest roentgenogram in 12 cases. Conclusions: Neurotuberculosis occurs with increased frequency in the age group of 1-5 years. Fever may be of short duration at presentation in contradiction to current medical literature. PEM is a predisposing factor for the development of the disease. A tuberculin sensitivity test may be negative in cases of neurotuberculosis. CSF analysis and neuroimaging are pivotal in the establishment of a diagnosis.